2009
DOI: 10.1016/j.bbadis.2008.12.003
|View full text |Cite
|
Sign up to set email alerts
|

(Pre)diabetes, brain aging, and cognition

Abstract: Cognitive dysfunction and dementia have recently been proven to be common (and underrecognized) complications of diabetes mellitus (DM). In fact, several studies have evidenced that phenotypes associated with obesity and/or alterations on insulin homeostasis are at increased risk for developing cognitive decline and dementia, including not only vascular dementia, but also Alzheimer's disease (AD). These phenotypes include prediabetes, diabetes, and the metabolic syndrome. Both types 1 and 2 diabetes are also i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
224
0
14

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 310 publications
(244 citation statements)
references
References 226 publications
(263 reference statements)
6
224
0
14
Order By: Relevance
“…In type 1 diabetes mellitus (T1DM), only a mild decrease of speed of information processing and psychomotor efficiency has been shown in nondemented subjects [31], while inT2DM, memory and executive functions have been found to be impaired [32]. One clue as to why T1DM and T2DM may differ in the progression of cognitive impairment is a potential interaction between diabetes and age [33]. In fact, T2DM is more prevalent with increasing age, and clinically relevant decreases in cognitive function are more likely to occur in elderly T2DM patients [34].…”
Section: Insulin Resistance Metabolic Syndrome and Cognitive Declinementioning
confidence: 99%
See 2 more Smart Citations
“…In type 1 diabetes mellitus (T1DM), only a mild decrease of speed of information processing and psychomotor efficiency has been shown in nondemented subjects [31], while inT2DM, memory and executive functions have been found to be impaired [32]. One clue as to why T1DM and T2DM may differ in the progression of cognitive impairment is a potential interaction between diabetes and age [33]. In fact, T2DM is more prevalent with increasing age, and clinically relevant decreases in cognitive function are more likely to occur in elderly T2DM patients [34].…”
Section: Insulin Resistance Metabolic Syndrome and Cognitive Declinementioning
confidence: 99%
“…In fact, T2DM is more prevalent with increasing age, and clinically relevant decreases in cognitive function are more likely to occur in elderly T2DM patients [34]. Another possible explanation for the differential effects on cognitive function is insulin resistance, a feature more prevalent in T2DM than in T1DM [33].…”
Section: Insulin Resistance Metabolic Syndrome and Cognitive Declinementioning
confidence: 99%
See 1 more Smart Citation
“…but more cerebrovascular lesions including microvascular lesions and white matter changes than subjects without DM [5, [21][22][23][24][25][26][27]. Vasculo-neural dysfunction has been suggested to represent a potential etiological linkage between DMT2 and AD [6,28], while others suggested that the association between DM and dementia is only partially mediated through cerebrovascular disease and that DM is associated independently with overal dementia among elderly, but not with AD or vascular dementia [29].…”
Section: Dmt2: Type 2 Diabetes Mellitus; Mci: Mild Cognitive Impairmentmentioning
confidence: 99%
“…Converging environmental and genetic risk factors trigger a pathophysiologic cascade, over decades, leads to Alzheimer pathology and dementia. [5] …”
Section: Observations Etiopathogenesis Of Admentioning
confidence: 99%